Teaching-learning processes in the university: students’ perspective - Cardona Henao, José Fernando (Rastros Rostros, 2016)
Introduction: the need to move from a teaching to a learning perspective makes the reflection appear in university classrooms from the education requirements for the twenty-first century, which calls for didactic strategies with open, flexible and interdisciplinary processes. From a descriptive research with a work unit of 1000 undergraduate students from three universities of Pereira, Colombia, a random probability probabilistic sample of 100 students of both sexes (30 from UniCatólica, 30 from UniAndina and 40 from Uni Libre), to whom a Likert questionnaire was applied, was carried out to measure teaching from three specific functions: 1) experimentation and collaborative work; 2) the correct teacher’s expression and gesture, and motivation to the student; 3) good interpersonal relationships and control of student learning. Each function was evaluated with ten indicators. Results: it was found that in the private universities of Pereira in undergraduate programs, the teaching-learning offered is an effective, dynamic and proactive process from the student’s perspective and from the analysis done to the didactic methodologies and strategies applied by teachers. Conclusions: in the universities of Pereira, in undergraduate programs, teaching-learning is offered based on experimentation and group collaborative work; From correct teachers’ expression and gesticulation as well as motivation of the student, from good interpersonal relations and control of the student’s learning. In the same way, it became evident that in these institutions, teaching-learning is an effective, dynamic and proactive process from the student’s perspective.